Risk indicators for untreated dental decay among Indigenous Australian children. Issue 4 (29th April 2019) - Ha, Diep Hong; Do, Loc Giang; Roberts‐Thomson, Kaye; Jamieson, Lisa
Abstract: Objective: To investigate risk indicators for untreated dental decay among Indigenous Australian children using a national representative sample. Methods: Data were from the National Child Oral Health Study 2012‐2014, which included a nationally representative sample of Indigenous Australian children aged 5‐14 years. Outcomes were the prevalence (% ds/DS >0) and severity (mean ds/DS) of untreated dental decay at the tooth surface level. Caries of the primary dentition was estimated among 5‐ to 10‐year‐olds, while that of the permanent dentition was among 8‐ to 14‐year‐olds. Independent variables included residential location, household income, frequency and age commencement of toothbrushing, sugar‐sweetened beverages (SSB) consumption, dental visiting and residential fluoridation status. Multivariable log‐Poisson regression models with robust standard error estimation were used to identify risk indicators for untreated decay. The complex sampling design was taken into account in all analyses. Results: There were 720 5‐ to 10‐year‐old and 736 8‐ to 14‐year‐old Indigenous children. Indigenous children experienced significant amount of untreated dental caries. Among 5‐ to 10‐year‐olds, % ds >0 was 43.1 (95% CI: 36.8‐49.6) and mean ds was 3.4 (95% CI: 2.4‐4.4). Among 8‐ to 14‐year‐olds, % DS >0 was 27.3 (22.3‐32.9), while mean DS was 0.8 (0.6‐1.0). In multivariable modelling, risk indicators for % ds >0 among 5‐ to 10‐year‐olds were low household income, commencing toothbrushing after 30 months of age, consuming 2+ cups of SSB per day and not residing in fluoridated areas. Risk indicators for mean ds among 5‐ to 10‐year‐olds included infrequent toothbrushing and consuming 2+ cups of SSB per day. Risk indicators for % DS >0 among 8‐ to 14‐year‐olds were low household income, while risk indicators for mean DS among 8‐ to 14‐year‐olds were residing in non‐capital city, low household income, consuming 2+ cups of SSB per day and not residing in fluoridated areas. Conclusion: Indigenous Australian children experienced significant amount of untreated dental caries. Risk indicators for untreated decay included demographic factors, socioeconomic factors, oral hygiene behaviours, dietary behaviours and environmental factors.